2021
DOI: 10.3390/agronomy11071378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sowing Mode on Lodging Resistance and Grain Yield in Winter Wheat

Abstract: For improving lodging resistance and increasing grain yield in wheat in the Yellow-Huai River Basin in China, different sowing modes have been investigated. Conventionally, the small-flat-plot sowing mode has been adopted in wheat cultivation. However, this sowing mode leads to heavy lodging and low land use efficiency. In this study, a new sowing mode, high-low-plot sowing mode with two more rows sowed on the high plot, was investigated. Two cultivars, Hengguan 35 and Jimai 44 were used for two seasonal field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Similarly, our results of reduced photosynthetic rate, leaf area, dry biomass, and yield were consistent with previous research conducted on wheat [7] and soya bean [8]. Waterlogging is undoubtedly reported to negatively impact a plant's physiological and biochemical response [16][17][18]. However, few studies also reported the innate adaptability of a plant against waterlogging stress [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, our results of reduced photosynthetic rate, leaf area, dry biomass, and yield were consistent with previous research conducted on wheat [7] and soya bean [8]. Waterlogging is undoubtedly reported to negatively impact a plant's physiological and biochemical response [16][17][18]. However, few studies also reported the innate adaptability of a plant against waterlogging stress [35].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, waterlogging is also a significant factor influencing the yield and quality of wheat. Waterlogging stress reduces yield, number of ears per square meter, grain weight, protein content, and levels of chlorophyll a and b while increasing proline levels [16]. Similarly, waterlogging induced a stress-activated antioxidant response system in Phalaris arundinacea [17].…”
Section: Introductionmentioning
confidence: 93%
“…The High-Low Seedbeds Cultivation (HLSC) pattern was developed by the Binzhou Academy of Agricultural Sciences, Shandong Province, China, aiming to solve the problems of low land utilization rate and light loss in the TI pattern [ 65 ]. In the HLSC, the land is integrated into a plane alternating between high and low beds, and wheat is planted on both beds.…”
Section: Effects Of Irrigation Management On Wheat Growth and Yieldmentioning
confidence: 99%
“…Furthermore, the WP of HLSC was 7.69% and 6.8% higher than that of TI and RC respectively [ 66 ]. In the study of Wu et al [ 65 ], two cultivars were used to investigate how HLSC mode increased grain yield and lodging resistance compared with TI. The results showed that the grain yield increase was mainly due to the enhanced spike number per area, while the lodging resistance was improved through the lowered plant height and the center of gravity height in the HLSC model.…”
Section: Effects Of Irrigation Management On Wheat Growth and Yieldmentioning
confidence: 99%
“…Lodging resistance was positively correlated with the wall thickness, the stem diameter, and the dry weight per centimetre, but the basal internode length was inversely correlated with lodging resistance (Tripathi et al, 2003). In addition, to characterise the lodging resistance of wheat plants, the lodging resistance index (LRI) is often used, and the relationships between LRI and other traits are well established (Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%